1970
DOI: 10.5424/sjar/20110901-214-10
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity among Spanish pea (Pisum sativum L.) landraces, pea cultivars and the World Pisum sp. core collection assessed by retrotransposon-based insertion polymorphisms (RBIPs)

Abstract: A total of 122 accessions of different wild and cultivated Pisum sp. were analysed using retrotransposon-based insertion polymorphisms (RBIP) markers. The Pisum materials included wild and cultivated (landraces and cultivars) materials from the World core collection of the John Innes Centre (JI) representing all generally recognized Pisum taxa, landraces materials from the Spanish core collection, and commercial pea cultivars largely sown in Spain. The overall polymorphism detected by RBIP marker was high and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 28 publications
(36 reference statements)
4
22
0
Order By: Relevance
“…sativum, while distances to the "wild" subspecies of P. sativum (transcaucasicum and jomardii) were the smallest found (3.55 and 3.16 respectively). This fact supports the model proposed by Martin-Sanz et al (2011), Smýkal et al (2011 and Kosterin and Bogdanova (2008) of a paraphyletic group, P. sativum subsp. elatius, within which all P. sativum are nested.…”
Section: Pumilio)supporting
confidence: 91%
See 1 more Smart Citation
“…sativum, while distances to the "wild" subspecies of P. sativum (transcaucasicum and jomardii) were the smallest found (3.55 and 3.16 respectively). This fact supports the model proposed by Martin-Sanz et al (2011), Smýkal et al (2011 and Kosterin and Bogdanova (2008) of a paraphyletic group, P. sativum subsp. elatius, within which all P. sativum are nested.…”
Section: Pumilio)supporting
confidence: 91%
“…Some examples of these are the investigations performed by Vershinin et al (2003), who studied the genetic structure and evolutionary history of the genus using SequenceSpecific Amplification Polymorphism (SSAP) markers; Ellis et al (2005) concluded that the exceptional DNA polymorphism within this genus is associated with recent genome expansion; Jing et al (2007) analysed sequence diversity of 39 dispersed gene loci and concluded that the different genes show large variation in diversity parameters, suggesting widely differing levels of selection and a high overall diversity level for the species. Martin-Sanz et al (2011) analysed accessions of different wild and cultivated Pisum sp. using retrotransposonbased insertion polymorphisms (RBIP) markers and found that landraces maintain a relatively high variability which is only partially represented in cultivars generally sown in Spain and are still a source of genetic variability for breeding new pea cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…We have evaluated here the iPBS-retrotransposon variability in a Turkish pea collection and some breeding lines. In the last decade, some research groups have studied the genetic diversity and relatedness in field pea by means of different DNA based molecular markers (Jing et al, 2007;Martin-Sanz et al, 2011;Ali et al, 2007;Jain et al, 2014;Ahmad et al, 2012;Kumari et al, 2013). Ahmad et al (2012) studied the genetic diversity among 35 pea accessions from Canada using microsattelite markers and found that 15 microsatellites were found to be polymorphic, amplifying a total of 41 alleles and were able to differentiate all 35 Pisum genotypes.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that Turkish pea revealed 6.1 average alleles per SSR locus (Sarıkamış et al, 2010). Similarly, 2 to 4 alleles per locus were reported in Spanish pea landraces (Martin-Sanz et al, 2011). Using SSR markers, Hagenblad et al (2014) reported 5 to 10 alleles in the Swedish garden pea.…”
Section: Discussionmentioning
confidence: 99%